Aliens and dragons: purposefully-framed play and non-standard learning methods in teaching evolutionary processes to primary school pupils - Antczak, Mateusz (Geologos, 2023)
Evolutionary processes lie at the base of the entire observable biodiversity, both at present and in the geological past (i.e., in the fossil record). For this reason, the teaching of evolution should receive more recognition than it currently has (e.g., in Poland) and become accurately applied from the early formal education stages onwards. To test the possibility of effective teaching of evolution to primary school pupils, workshops using non-standard learning methods (‘purposefully-framed play’) were organised during childrens’ university (UNIKIDS) courses of one-hour sessions for 33 groups, comprising several to 20 participants, aged 7 to 12. The final task for all participants was to predict future evolutionary processes by creating new species adapted to given environmental factors. Pupils effectively completed this task, but a few misconceptions also become clear. These workshop scenarios suggest that evolution can be taught effectively at least in extracurricular settings to primary school pupils, but for a detailed insight, a quantitative analysis and application of such scenarios in school programmes should be tested in future.